Security Scanner For Web Applications Case Study: Learning Management System - Rian Andrian; Ahmad Fauzi (JOIN (Jurnal Online Informatika), 2019)
In software engineering, web applications are software that are accessed using a web browser through a network such as the Internet or intranet. Web applications are applications that can be relied on by users to do many useful activities. Despite the awareness of web application developers about safe programming practices, there are still many aspect in web applications that can be exploited by attacker. The development of web applications and the Internet causes the movement of information systems to use them as a basis. Security is needed to protect the contents of web applications that are sensitive and provide a safe process of sending data, therefore application security must be applied to all infrastructure that supports web applications, including the web application itself. Most organizations today have some kind of web application security program or try to build/ improve. But most of these programs do not get the results expected for the organization, are not durable or are not able to provide value continuously and efficiently and also cannot improve the mindset of developers to build/ design secure web applications. This research aims to develop a web application security scanner that can help overcome security problems in web applications.